Fiscal and monetary problems in developing States : proceedings of the third Rehovoth Conference - Krivine, David (New York : Praeger, 1967)
The book contains the papers presented at the 1965 conference sponsored by the Continuation Committee of the Rehovoth Conference in cooperation with the Eliezer Kaplan School of Economics and Social Sciences in the Hebrew University of Jerusalem. The aim of the conference was to see how the gap between the rich countries and the poor countries can be abridged through science and technology.
Includes bibliographical footnotes.
usc 14/07/2018
Loans
Keywords: Finance; Monetary problems; Fiscal problems; Developing countries